Recent Progress in Our Understanding of Phase Stability, Atomic Structures and Mechanical and Functional Properties of High-Entropy Alloys - Inui, Haruyuki; Kishida, Kyosuke; Chen, Zhenghao (MATERIALS TRANSACTIONS, 2022)
This paper reviews a current trend and recent progress in research on phase stability, atomic structures, mechanical and functional properties of high-entropy alloys. The survey is carried out based partly on the special issue published in April, 2020, in Materials Transactions (Vol. 61, No. 4). Research on high-entropy alloys has spread worldwide since the year of 2004, as many of them exhibit attractive properties for structural and functional applications, which have never been achieved in conventional alloys. Significant progress has been made in recent years in our understanding of high-entropy alloys in terms of processing, characterization, modeling and simulation, and so on. Some of them are briefly described in this paper.